Analisa Produk Tabungan BSM Dalam Menarik Minat Nasabah - Khodijah Ishak; Ida Afrida Ningsih (JPS (Jurnal Perbankan Syariah), 2020)
Bank Syariah Mandiri Sub-Branch Office Dumai Sukajadi is one of the banks operating based on sharia principles offering fundraising products and one of them is tabungan BSM . The tabungan BSM are based on sharia principles with the mudharabah muthlaqah agreement. This research uses primary data and secondary data. The results showed that the marketing strategy of tabungan BSM products to attract customers of Bank Syariah Mandiri Dumai Sukajadi Sub-Branch Office has been going well, from conducting promotions, socializing, distributing brochures and participating in certain events. In addition, the presence of Bank Syariah Mandiri Dumai Sukajadi Sub-Branch Office is very helpful for customers to open various kinds of savings provided by the Bank Syariah Mandiri Dumai Sukajadi Sub-Branch Office.